2016
DOI: 10.1074/jbc.m116.745513
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Hydrophobic Core in Gαi1 Regulates G Protein Activation and Release from Activated Receptor

Abstract: G protein-coupled receptor-mediated heterotrimeric G protein activation is a major mode of signal transduction in the cell. Previously, we and other groups reported that the ␣5 helix of G␣ i1 , especially the hydrophobic interactions in this region, plays a key role during nucleotide release and G protein activation. To further investigate the effect of this hydrophobic core, we disrupted it in G␣ i1 by inserting 4 alanine amino acids into the ␣5 helix between residues Gln 333 and Phe 334 (Ins4A). This extends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…The structural basis for GPCR-dependent G protein activation had challenged the field for decades but was revealed in the past 8 y by a series of landmark structural studies (14)(15)(16)(17)(18). These studies have demonstrated that one of the key mechanisms of G protein activation by GPCRs involves perturbation of the so-called hydrophobic core (19,20) of the Gα GTPase domain, which is mediated by displacement of the Cterminal α5 helix and insertion of the GPCR's intracellular loop 2 (14)(15)(16)(17)(18).…”
Section: Structural Basis For Gpcr-independent Activation Of Heterotrmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural basis for GPCR-dependent G protein activation had challenged the field for decades but was revealed in the past 8 y by a series of landmark structural studies (14)(15)(16)(17)(18). These studies have demonstrated that one of the key mechanisms of G protein activation by GPCRs involves perturbation of the so-called hydrophobic core (19,20) of the Gα GTPase domain, which is mediated by displacement of the Cterminal α5 helix and insertion of the GPCR's intracellular loop 2 (14)(15)(16)(17)(18).…”
Section: Structural Basis For Gpcr-independent Activation Of Heterotrmentioning
confidence: 99%
“…The most striking increase in dynamics was observed in the C-terminal region of Sw-I and the β2-β3 strands ( Fig. 6 B and C), which normally pack against the α1and α5-helices of Gαi to form the hydrophobic core (20) of the GTPase domain. When simulations were run in the presence of the His-tag linker, the dynamics of Sw-II was unchanged with respect to the GIV-bound state, the high mobility of Sw-III was restored to the GDP-only level, and the GIV-induced increase in Sw-I and β2-β3 strand dynamics was partially negated, in agreement with a potential role of the His-tag linker in stabilizing GIV-GEM-bound Gαi and facilitating its crystallization (SI Appendix, Fig.…”
Section: Molecular Dynamics Simulations Reveal Giv-induced Rearrangemmentioning
confidence: 99%
“…proteins dissociate from GPCRs immediately after GTP loading, making affinity purification problematic. We therefore made WT and Q307K Gi1 with the 4 alanine insertion (hereafter ins4A) in helix !5 that increases affinity for GPCRs even in the presence of GTP 19 . These G!…”
Section: Identification Of the Upstream Gpcrmentioning
confidence: 99%
“…By validation of calculated infrared (IR) spectra from quantum-mechanics/molecular-mechanics (QM/MM) calculations against the experimental values that were measured with natural GTP it will be possible to clarify the structure of the native binding pocket of G α i1 with sub-Å resolution and charge shifts that are important for catalysis can be obtained. Furthermore calculation of the inactive GDP state might clarify the discussion if the inactive state of G α i1 does or does not carry a Mg 2+ ion (PDB: 1GP2 , 5KDO ) ( 9 , 10 , 11 ). There are several examples for the calculation of GTPase IR-spectra in the literature, e.g., for the small GTPases Ras ( 12 , 13 , 14 , 15 , 16 , 17 ), Ran ( 18 ), Arl ( 19 ), and others.…”
Section: Introductionmentioning
confidence: 99%